(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
Sensitivity to cultural differences is not just a trend, but a key skill for success in the modern hospitality industry. The development of this skill among employees allows companies to provide high-quality service, strengthen their reputation, attract more customers, increase efficiency and create a positive work environment. Therefore, developing this skill is not just a good solution, but a necessity for thriving in the modern hospitality industry.